The relevant intervention strategies for improving medication adherence of diabetic patients. - Cliffton Akoi; Md. Mizanur Rahman; Mohd Syafiq Abdullah (Universiti Kebangsaan Malaysia, 2013)
Medication adherence is very important for the effective treatment or control of various health problems, including chronic disease like diabetes mellitus(DM). However, medication non-adherence among diabetic patients on follow-up treatment is still a global health problem. This study aimed to identify factors associated with medication adherence and to determine methods on how it could be improved.